2011
DOI: 10.4236/jbnb.2011.24049
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Synthesis of Butyl Ferulate by Silica-Immobilized Lipase in a Non-Aqueous Medium

Abstract: Butyl ferulate was synthesized using a silica-immobilized commercial lipase (Steapsin) in dimethylsulfoxide (DMSO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…5 . In a previous study, silica bound commercial lipase, Steapsin showed a moderate increase in the synthesis of isopropyl ferulate with 100 mg/mL of molecular sieves in a 2 mL of reaction mixture 38 . It appears that an excess concentration of molecular sieves completely removed even traces of water molecules from the reaction mixture, thus rendering the bound-lipase relatively ineffective to perform the esterification reaction which resulted in a gradual decline in the ester yield.…”
Section: Effect Of Reaction Temperature On the Synthesis Of Methyl Samentioning
confidence: 86%
See 3 more Smart Citations
“…5 . In a previous study, silica bound commercial lipase, Steapsin showed a moderate increase in the synthesis of isopropyl ferulate with 100 mg/mL of molecular sieves in a 2 mL of reaction mixture 38 . It appears that an excess concentration of molecular sieves completely removed even traces of water molecules from the reaction mixture, thus rendering the bound-lipase relatively ineffective to perform the esterification reaction which resulted in a gradual decline in the ester yield.…”
Section: Effect Of Reaction Temperature On the Synthesis Of Methyl Samentioning
confidence: 86%
“…Frequent encountering of substrate into the active site might have caused its distortion, thus reducing its catalytic efficiency either partially or fully. In previous studies, the synthesis of isopropyl ferulate and butyl ferulate by silica bound commercial lipase, Steapsin was achieved in short periods of 3 h, and 6 h, respectively 37,38 . In these studies, a good yield of the respective ester s was noted in the 1st and 2nd cycles of esterification/reuse but, ultimately, the product yield continued to decline with successive cycles of reuse.…”
Section: Reusability Of Immobilized Enzymementioning
confidence: 99%
See 2 more Smart Citations
“…Any water that reaches the enzyme for participation in the reaction must difuse from the bulk emulsion. Thus, to avoid difusional limitations, the oil phase must be well saturated with water [105].…”
Section: Inluence Of Water Activitymentioning
confidence: 99%